Information of System Monitoring by Network Oparation Center - Amat Basri; Alexius Hendra Gunawan (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2021)
Network Operation Central (NOC), an Enterprise Service Division which functions to carry out monitoring and supervision activities of Telkom network equipment located at Plaza Indonesia. Customer satisfaction is the basis and goal that is always hoped for by customers, by carrying out maintenance activities of network devices, and carrying out solutions when problems occur in customers are expected to be an efficient and effective service quality standard. This study wants to know that the construction of a monitoring system for NOC work activities can improve service quality. The quality of this system can be measured using the ISO9126 model, by adapting four characteristics of software quality: functionality, reliability, usability, and efficiency. The system development model uses the Rapid Application Development (RAD) and Joint Application Development (JAD) models. Researchers will analyze and design the system using the Unified Model Language (UML), then by coding with PHP programming and MySQL databases, and data collection using a questionnaire, and system testing using the Blackbox Testing model. Based on testing using ISO 9126 the results are functionality (80%), reliability (79%), usability 86%), and efficiency (79%). Overall the result was 81% (good).